Brillouin light scattering study of magnetic-element normal modes in a square artificial spin ice geometry - Li, Y; Gubbiotti, G; Casoli, F; Gonçalves, F J T; Morley, S A; Rosamond, M C; Linfield, E H; Marrows, C H; McVitie, S; Stamps, R L (Journal of physics. D, Applied physics, 2017)
We report the results, from experimental and micromagnetic studies, of the magnetic normal modes in artificial square spin ice systems consisting of ferromagnetic-monodomain islands. Spin-wave properties are measured by Brillouin light scattering. The mode spectra contain several branches whose frequencies are sensitive to the magnitude and in-plane orientation of an applied magnetic field. We also identify soft modes that exhibit different behaviours depending on the direction of the applied magnetic field. The obtained results are well described with micromagnetic simulations of independent magnetic elements arranged along two sublattices.